2021
DOI: 10.1038/s41598-021-87284-x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and population structure of advanced clones selected over forty years by a potato breeding program in the USA

Abstract: Knowledge regarding genetic diversity and population structure of breeding materials is essential for crop improvement. The Texas A&M University Potato Breeding Program has a collection of advanced clones selected and maintained in-vitro over a 40-year period. Little is known about its genetic makeup and usefulness for the current breeding program. In this study, 214 potato clones were genotyped with the Infinium Illumina 22 K V3 Potato Array. After filtering, a total of 10,106 single nucleotide polymorph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 75 publications
5
51
1
Order By: Relevance
“…Previous studies showed population bottlenecks and/or balancing selection when positive Tajima’s D values were determined for a population [ 39 , 40 ]. The positive Tajima’s D values of all tea populations here suggest that they all underwent population bottlenecks and/or balancing selection (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed population bottlenecks and/or balancing selection when positive Tajima’s D values were determined for a population [ 39 , 40 ]. The positive Tajima’s D values of all tea populations here suggest that they all underwent population bottlenecks and/or balancing selection (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies demonstrated that positive Tajima’s D values indicated population bottlenecks and/or balancing selection [ 39 , 40 ]. Positive Tajima’s D values were observed in all populations in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…First, genotyping-by-Sequencing (GBS) is a now popular method of HTG in crops including potato (Uitdewilligen et al, 2013;Bastien et al, 2018). GBS has been applied effectively in genome-wide studies in potato on genetic diversity and population structure (Pandey et al, 2021), QTL mapping (Schönhals et al, 2017), and SNP discovery (Caruana et al, 2019). Secondly, the SNP array-based HTG system has already been developed and applied in potato for population structure and SNP discovery using 20K SNP array (Vos et al, 2015(Vos et al, , 2017, 22K SNP array for starch phosphorylation (Khlestkin et al, 2019), and 12K SNP array (Illumina) for genetic diversity in the genbank of the International Potato Centre, Peru (Ellis et al, 2018).…”
Section: Genome-wide Genetic Diversity and Association Studies Using ...mentioning
confidence: 99%
“…Previous research found that market class was a good biological explanation to subpopulations in cultivated tetraploid potato (Hirsch et al 2013;Igarashi et al 2019;Pandey et al 2021). In this study, all potato accessions are classi ed as table potato with one exception, the cultivar 'Kuras' from the population of cultivars grown in Sweden today.…”
Section: Discussionmentioning
confidence: 92%